A long ascent to the right for health - Šarmanov, Turegeljdy Šarmanovič (Atamura Publishes, 1998)
This publication focuses on public health care, primary health care and some health care systems. Intended for professionals.
Keywords: Global Health; poskytování zdravotní péče; celosvětové zdraví; Kazachstán; veřejné zdravotnické služby; Primary Health Care; Right to Health; právo na zdraví; veřejné zdravotnictví; Kazakhstan; primární zdravotní péče; Community Health Services; Delivery of Health Care